Crop production in Ethiopia: Regional patterns and trends - Taffesse, Alemayehu Seyoum; Dorosh, Paul A.; Gemessa, Sinafikeh Asrat (University of Pennsylvania Press, 2012)
Ethiopia’s crop agriculture is complex, involving substantial variation in crops grown across the country’s different regions and ecologies. Five major cereals (teff, wheat, maize, sorghum, and barley) are the core of Ethiopia’s agriculture and food economy, accounting for about three-fourths of the total area cultivated, 29 percent of agricultural gross domestic product (GDP) in 2005/06 (14 percent of total GDP), and 64 percent of calories consumed (FAO various years). There has been substantial growth in cereals in terms of area cultivated, yields, and production since 2000, but yields are low by international standards, and overall production is highly susceptible to weather shocks, particularly droughts. Thus, raising production levels and reducing their variability are essential aspects of improving food security in Ethiopia, both to help ensure adequate food availability and to increase rural household incomes.